Availability of urinary albumin measurement in Southern Brazilian laboratories - Soares, Ariana Aguiar; Cheuiche, Amanda Veiga; da Silva, Alexandre Sauer; Jung, Larissa Petermman; Camargo, Joiza Lins; Silveiro, Sandra Pinho (Clinical and Biomedical Research, 2015)
Introduction: Diabetic kidney disease (DKD) is the leading worldwide cause of end-stage renal disease. The current recommendation is to screen for DKD by evaluating estimated glomerular filtration rate (eGFR) and measuring urinary albumin (UA) levels in a spot sample. The aim of this study was to evaluate the availability of UA measurement in Southern Brazilian laboratories. Methods: A cross-sectional study was conducted to assess the routine use of UA in all laboratories registered in the State Pharmacy Council ofRio Grande do Sul, the southernmost state ofBrazil. Data was collected by mail, e-mail, telephone, or personal interview. A sample size of at least 384 laboratories was necessary to achieve 5% precision at a 95% confidence level based on a fixed proportion of 0.5. Results: Eight hundred and eighty laboratories currently registered in the state were invited to participate in the study; 548 (62%) answered the technical specification questionnaire. Only 306 (55%) of the 548 surveyed laboratories performed UA measurements. The laboratories were also required to provide the number of UA measurements performed per day, which ranged from less than one per week to 65 per day. Conclusion: The availability of UA measurements is undesirably low inSouthern Brazil. This demonstrates the urgent need to increase the availability of this important test. It also reveals the gap between the current guidelines and the awareness about them among health care professionals.